Diagnostic and prognostic value of STAP1 and AHNAK methylation in peripheral blood immune cells for HBV-related hepatopathy - Sun, Libo; Lu, Junfeng; Li, Kang; Zhang, Haitao; Zhao, Xiaofei; Li, Guangming; Li, Ning (Frontiers in Immunology, 2023)
Although we had identified that the methylation of AHNAK was a good diagnostic marker for hepatopathy, here we speculate that there was also another marker, STAP1, whose methylation also involved in the detection of hepatopathy. We investigated the methylation levels of the AHNAK and STAP1 in peripheral blood mononuclear cells of chronic hepatitis B (CHB) patients, compensatory liver cirrhosis (CLC) patients, decompensated liver cirrhosis (DCLC) patients, hepatocellular carcinoma (HCC) patients and healthy controls by methylation-specific PCR. We also evaluated the differences and changes of methylation and expression of AHNAK and STAP1 at different stages of liver disease using the TCGA and GEO public datasets. Methylation level of STAP1 in PBMC was positively correlated with the course of liver cancer. The combination of AHNAK and STAP1 methylation was able to predict differrent HBV related hepatopathy. The GEO datasets also supported that the methylation of AHNAK and STAP1 was associated with different types of hepatopathy. The TCGA data showed that the levels of methylation and expression of STAP1 were down-regulated in HCC. We also found the STAP1 methylation level in PBMC and T cells was associated with age, gender, drinking and anti-HBeAg. Hyper-methylation of STAP1 was correlated with the poor prognosis of patients but its expression had no association. We concluded that combination of AHNAK and STAP1 methylation in peripheral blood immune cells can be used as a diagnostic marker for HBV related hepatopathy and STAP1 methylation may be a potential prognostic marker for HBV related HCC. Our clinical study registration number was ChiCTR2000039860.